Design of highly sensitive complementary metamaterial‐based microwave sensor for characterisation of dielectric materials. Issue 15 (10th November 2020) - Samad, Abdul; Hu, Wei Dong; Shahzad, Waseem; Raza, Hamid; Ligthart, Leo P.
Abstract : Metamaterial‐based double‐slit complementary split rectangular resonator sensor is proposed for the characterisation of dielectric properties of the materials under test (MUTs). The proposed sensor is designed and simulated on the CST microwave studio software using a low‐cost substrate FR4. An array of three identical resonators is etched in the ground plane of the sensor to achieve a single and deep notch of −58.7 dB in the transmission coefficient ( S 21 ) at the resonant frequency of 7.01 GHz, which is the novelty of the proposed sensor. A deep and single resonant frequency band has a significant role in the precise measurement of the dielectric properties of the MUTs. The effective constitutive parameters are extracted from the S ‐parameters. An equivalent circuit model is suggested that describes the overall behaviour of the sensor. The sensor is fabricated on the FR4 substrate and measured through the vector network analyser (N5224B) by placing the standard materials. The parabolic equation for the proposed sensor is formulated to approximate the permittivity of the MUTs. A very small percentage of error, 0.77, is found which shows high accuracy of the sensor. This methodology is efficient, simple in fabrication, and reduces cost and computational time also.